Archeologia, Osservazione della Terra e Intelligenza Artificiale: il contributo dell’Agenzia Spaziale Ita liana per il Pat rimonio Culturale - Roberto Angelone (Archeomatica)
Remote sensing in the archaeological field has proved to be an important tool for the identification, documentation and conservation of archaeological sites. The use of SAR data is constantly increasing in the monitoring of archaeological sites. COSMO-SkyMed satellites funded by the Italian Space Agency, offer high-resolution images and the ability to operate day and night, in any weather condition. Remote sensing and Artificial Intelligence offer new perspectives for archaeology. Through the integration of human skills and advanced technologies new opportunities can be offered to deepen knowledge of the past and preserve our archaeological heritage for future generations.